Evaluation of BaCo0.4Fe0.4Zr0.2−xNixO3−δ perovskite cathode using nickel as a sintering aid for IT-SOFC. Issue 24 (16th April 2021) - Irshad, Muneeb; Khalid, Mehak; Rafique, Muhammad; Ahmad, Naveed; Siraj, Khurram; Raza, Rizwan; Sadiq, Muhammad; Ahsan, Muhammad; Ghaffar, Abdul; Ashfaq, Amina
Abstract : Electrochemical performance of BaCo0 .4 Fe0 .4 Zr0.2− x Ni x O3− δ at 600 °C. Abstract : In this research work, BaCo0 .4 Fe0 .4 Zr0.2− x Ni x O3− δ ( x = 0, 0.01, 0.02, 0.03, 0.04) perovskite cathode material for IT-SOFC is synthesized successfully using a combustion method and sintered at low temperature. The effects of nickel as a sintering aid on the properties of BaCo0 .4 Fe0 .4 Zr0 .2 O3− δ are investigated through different characterization methods. The addition of nickel increased the densification and grain growth at a lower sintering temperature 1200 °C. XRD analysis confirms a single phase of BaCo0 .4 Fe0 .4 Zr0 .2 O3− δ, and an increase in crystalline size is observed. SEM micrographs show formation of dense microstructure with increased nickel concentration. TGA analysis revealed that BaCo0 .4 Fe0 .4 Zr0.2− x Ni x cathode materials are thermally stable within the SOFC temperature range, and negligible weight loss of 2.3% is observed. The bonds of hydroxyl groups and metal oxides are confirmed for all samples through FTIR analysis. The highest electrical properties are observed for BaCo0 .4 Fe0 .4 Zr0.2− x Ni x ( x = 0.04) due to increased densification and electronic defects compared to other compositions. The maximum power density of 0.47 W cm −2 is obtained for a cell having cathode material BaCo0 .4 Fe0 .4 Zr0.2− x Ni x ( x = 0.02) owing to its permeable and well-connected structure compared to others.